2016
DOI: 10.1038/srep33601
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron microbeam irradiation induces neutrophil infiltration, thrombocyte attachment and selective vascular damage in vivo

Abstract: Our goal was the visualizing the vascular damage and acute inflammatory response to micro- and minibeam irradiation in vivo. Microbeam (MRT) and minibeam radiation therapies (MBRT) are tumor treatment approaches of potential clinical relevance, both consisting of parallel X-ray beams and allowing the delivery of thousands of Grays within tumors. We compared the effects of microbeams (25–100 μm wide) and minibeams (200–800 μm wide) on vasculature, inflammation and surrounding tissue changes during zebrafish cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 37 publications
0
50
0
1
Order By: Relevance
“…2A), indicating its potential to act as a vascular disruption agent in radio-oncology. Studies on chick chorioallantoic membrane and zebrafish caudal fin regeneration models, showing 2 types of immature vessels, demonstrated that MRT induced notable morphologic and functional damage 10 and severely impaired vascular perfusion 12 of immature blood vessels. Two main mechanisms were identified: (1) direct disruption of immature capillaries along the beam path, which caused endothelial cell detachment and consequent folding into the lumen; and (2) local adhesion of blood cells at the site of vascular damage.…”
Section: Discussionmentioning
confidence: 99%
“…2A), indicating its potential to act as a vascular disruption agent in radio-oncology. Studies on chick chorioallantoic membrane and zebrafish caudal fin regeneration models, showing 2 types of immature vessels, demonstrated that MRT induced notable morphologic and functional damage 10 and severely impaired vascular perfusion 12 of immature blood vessels. Two main mechanisms were identified: (1) direct disruption of immature capillaries along the beam path, which caused endothelial cell detachment and consequent folding into the lumen; and (2) local adhesion of blood cells at the site of vascular damage.…”
Section: Discussionmentioning
confidence: 99%
“…Vasculature organization of the irradiated tissue depends on the stage of tissue maturation and as a result, determines tolerance to MRT. Models of immature vasculature have been the regenerating fin of the zebrafish [70] and the early chick chorioallantoic membrane [71]. The susceptibility of immature vessels to MRT-induced damage is significantly higher than the mature vessels which show very little post-MRT alterations (vascular lesions, reduced perfusion) when the MRT spacing is kept below 200 µm [71].…”
Section: Vasculaturementioning
confidence: 99%
“…No changes in animal behaviour have been observed [72]. Data from chick chorioallantoic membrane [71] and zebrafish fin regeneration [70] models demonstrate the disruptive vascular effect of MRT on immature blood vessels. Work in adult organisms confirmed that the disruptive vascular effects of MRT depend on the vascular maturation status.…”
Section: Mrt Selectively Disrupts Immature Blood Vesselmentioning
confidence: 99%
“…Redundant cortical functions may be thus more efficient in the closed context of moduli, as in control animals where the network redundancy is resilient to the low grade degradation from MB (Gao, Barzel, and Barabási 2016). The alternative hypothesis of regeneration of properties appears weaker, in that no specific neurogenesis after irradiation has been observed in the literature (Brönnimann et al 2016) (except for poor potential cell extensions as shown in Figure 7). The irradiation induces also local vascular regenerative episodes where signs of novel vessel branches transpassing narrower MB tracks (25 µm, 500 Gy) have been observed (Serduc et al 2008).…”
Section: Discussionmentioning
confidence: 94%